2000
DOI: 10.1159/000027483
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Induced Retinopathy in the Newborn Rat: Morphological and Immunohistological Findings in Animals Treated with Topical Timolol Maleate

Abstract: Oxygen-induced retinopathy (OIR) similar to that seen in premature infants can be produced in newborn rats by exposure to 80% oxygen for the first 5 days of life, with subsequent recovery for 7 days in a room air environment. Previous studies have shown that the latter phase is associated with degeneration of retinal astrocytes. In the absence of astrocytes, the vascular endothelial growth factor (VEGF) is produced by the neurons of the inner retina. In this study, immunohistochemical methods were used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In the rat, topical timolol (a β-adrenergic receptor antagonist with highest affinity for the β2-adrenoreceptor 36 ) diminishes retinal neovascularization during OIR 37 . More recently, the Bagnoli group showed that propranolol 32 and a selective β2-adrenoreceptor blocker 33 can both attenuate retinal neovascularization during OIR in mice by decreasing VEGF production.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, topical timolol (a β-adrenergic receptor antagonist with highest affinity for the β2-adrenoreceptor 36 ) diminishes retinal neovascularization during OIR 37 . More recently, the Bagnoli group showed that propranolol 32 and a selective β2-adrenoreceptor blocker 33 can both attenuate retinal neovascularization during OIR in mice by decreasing VEGF production.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this effect to a decreased intraocular pressure induced by topical timolol as occurs in glaucoma patients, thus improving ocular perfusion pressure. 20 Systemic BABA are frequently used in the clinical practice to treat cardiac arrhythmia, hypertension, migraine, and hyperthyroidism among other conditions. Propanolol has been used to treat neovascular conditions such as infantile capillary hemangiomas [21][22][23][24][25][26][27][28][29][30][31] and retinopathy of prematurity 32 ; clinical trials are underway to elucidate the effect of these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol does not affect the VEGF retinal levels in rats with DR (Zheng et al 2007). In contrast, a decrease in VEGF has been observed in the retinas of neonatal OIR rats, in which a reduction in intraocular pressure induced by the b-AR antagonist timolol diminishes the severity of OIR (Ricci et al 1991(Ricci et al , 1995(Ricci et al , 2000. This discrepancy might be explained by either the different drug administration routes or different dosages or the possibility that the control of angiogenesis by b-ARs can be regulated by distinct mechanisms in OIR and DR.…”
Section: The Role Of B-adrenergic Receptors (B-ars)mentioning
confidence: 96%
“…2007). In contrast, a decrease in VEGF has been observed in the retinas of neonatal OIR rats, in which a reduction in intraocular pressure induced by the β‐AR antagonist timolol diminishes the severity of OIR (Ricci et al. 1991, 1995, 2000).…”
Section: The Role Of β‐Adrenergic Receptors (β‐Ars)mentioning
confidence: 98%